A case report and literature review of autism and attention deficit hyperactivity disorder in paediatric chronic pain - Wiwe Lipsker, C.; von Heijne, M.; Bolte, Sven; Wicksell, R. (Wiley-Blackwell Publishing Ltd., 2018)
©2018 Foundation Acta Pædiatrica. Psychiatric disorders are common in paediatric patients with chronic pain, but the overall prevalence of comorbid neurodevelopmental disorders is unclear. We report on a case of severe chronic pain in a child with undiagnosed comorbid autism spectrum disorder and attention deficit hyperactivity disorder, where significant improvements in pain and function occurred following methylphenidate medication and parental behavioural training. Conclusion: The inclusion of behavioural assessment and screening for neurodevelopmental comorbidity may be essential in addressing complex paediatric chronic pain.